Measures of personality and social psychological attitudes - Robinson, John P.; Shaver, Phillip R.; Wrightsman, Lawrence S.; Andrews, Frank M. (Measures of social psychological attitudes, 1991)
This is an essential reference book for any social scientist or student who uses measures of attitude or personality in his or her research. The earlier version, published twenty years ago, was to be found on the shelf of virtually everyone who worked in the field.